Characteristics of Charcoal Briquettes, Activated Charcoal, and Liquid Smoke from Rice Husk (Oriza sativa L.) - Rindayatno; Finsya Annisa Cahya Shafiera; Baktiriani Banda Padang; Tersisius Tigang; Agus Nur Fahmi (Formosa Journal of Sustainable Research, 2023)
Rice husk (Oriza sativa L.) was studied in three products, namely charcoal briquettes, activated charcoal and liquid smoke. Aims to know and analyze the characteristics of the three products. Making charcoal briquettes through the forming process of rice husk charcoal powder then tested for density, moisture content, compressive strength, volatile matter, ash content, fixed carbon content, and heating value. Rice husk charcoal powder activated by soaking for 5 hours in 5% hydrochloric acid (HCl) then tested for its adsorption on spills of used lubricant. Liquid smoke from rice husk is obtained by pyrolysis process and multilevel purification and then the yield, pH value, specific gravity, and color are measured. Rice husk charcoal briquettes had the following values: density 0,601 g/cm3, moisture content 5,596%, compressive strength 8,665 kg/cm2, volatile matter content 25%, ash content 31,8%, fixed carbon content 43,2% and heating value 4.477 cal/g. Rice husk activated charcoal has an adsorption capacity of used lubricants up to 3,27 times stronger than activated charcoal with a fixed carbon content of 44,5%. Grade 3 rice husk liquid smoke has a yield value of 8,40%; pH 4,27; specific gravity 0,997; and black color. Grade 2 has a yield value of 5,20%; pH 3,41; specific gravity 1,003; and light brown. Grade 1 has a yield value of 3,87%; pH 3,24; specific gravity 0,997; and clear white color